Potential and unrealized future possibilities of browntop millet in the food sector - Singh, Shivani; Suri, Sukhneet; Singh, Ranjana (Frontiers in Sustainable Food Systems, 2022)
Browntop millet (BTM) is small-seeded annual grass cultivated as grain crop, primarily on the marginal lands in dry areas in temperate, subtropical and tropical regions. It is increasingly receiving attention of the scientific community. Aim of this systematic review is to study the physiochemical, sensory, functional and nutritional properties as well as health benefits of browntop millet. This paper is based on quantitative and qualitative secondary data obtained from 71 out of 208 descriptive and scientific literature reviewed and analyzed from the national and international electronic platforms. The scientific literature based on browntop millet has been found scanty. According to the few studies available energy ranges from 338.0 kcal to 368.62 kcal. The carbohydrate, crude fiber and fat content of BTM is 71.32 gm, 8.06–16.08%, 1.89 gm, respectively. Protein is between 11.64% and 10.72%. Browntop millet contains phytochemicals such as flavonoids, quinones, tannins, and resin. There is galore scope for development and standardization of value added products made from browntop millets such as ready to eat foods (cookies, bars, deserts, etc) and ready to cook foods (idli mix, poha, etc) in which the millet can be used in combination with other cereal grains. Thus, browntop millet holds great potential in alleviating food and nutrition insecurity. It has good nutritional value. It can be used for the prevention and management of several non-communicable diseases. In order to make this smart food popular among farmers and consumers, systematized studies in the field of agriculture, nutrition, toxicology, naturopathy and biomedical sciences need to be done and documented properly. From ancient times BTM has been used in many forms such as forage, staple food or in many traditional dishes. An e-repository can be made of the traditional Indian foods made from BTM to popularize its use among the younger generations.